MHC Disparate Resting B Cells Are Tolerogenic in the Absence of Alloantigen-Expressing Dendritic Cells. (28th November 2012) - McFarland, Hugh I.; Tsuji, Kazuhide; Mason, Karen P.; Rosenberg, Amy S.
Abstract : Resting B cell (rB) populations have been shown to tolerize to soluble proteins and to minor-H but not to MHC alloantigens. We speculated that the reason for failing to tolerize to MHC alloantigen is that the few remaining dendritic cells (DCs) contaminating purified rB cell populations efficiently activate MHC allospecific T cells which are present at a higher frequency than T cells specific for minor-H alloantigen and soluble proteins. We established that MHC disparate rB cells are indeed tolerogenic when devoid of DC populations, as parental strain mice showed delayed D d skin graft rejection when infused with rB cells from mice in which MHC class I D d alloantigen was specifically targeted to T and B cells (CD2-D d transgenic mice). In contrast, treatment of parental strain mice with allogeneic rB cells purified from MHC-D d transgenic mice, in which D d is ubiquitously expressed, including DCs, induced accelerated D d graft rejection. We also showed that adding only 5, 000 D d expressing DCs to CD2-D d rB cells abrogated the tolerogenic effect. Surprisingly, allogeneic rB cells prolonged graft survival in D d -primed mice. Thus, MHC disparate rB cells are tolerogenic and their failure to delay graft rejection can be explained by contaminating allogeneic DCs.